ACTIVIDADES LÚDICAS PARA MEJORAR EL ESTADO FÍSICO EN LOS ADULTOS MAYORES DEL RECINTO CANDILEJO DEL CANTÓN SALITRE. - BUSTAMANTE ESCOBAR ADONIS LEONEL (2024)
present research focuses on recreational activities to improve the physical condition of older adults in the Candilejo precinct of Cantón Salitre, the main objective is to contribute to improve the physical condition of these people. It is expected that the research will become a great contribution to the field of physical education and will provide professionals in the area with a useful resource to improve the physical condition of older adults, achieving their well-being. The instruments used were the survey and the interview, which were able to determine that most of the people do not perform ludic activities or physical activities but that they would be willing to practice them, they only need someone to instruct and motivate them. The research was carried out through a mixed approach, using the quantitative and qualitative methods; qualitative to collect opinions and perceptions of older adults and their families with respect to recreational activities and quantitative to obtain numerical data from the information obtained. The combination of these methods will provide results and will contribute to propose a program of recreational activities to improve the physical condition of older adults in this sector.